Ophiorrhiza debiana (Rubiaceae, Rubioideae), a new species from North-East India - Hareesh, Vadakkoot Sankaran; Joe, Alfred; Sabu, Mamiyil (Phytotaxa, 2017)
A new species of Ophiorrhiza is described from Arunachal Pradesh, North-East India. Ophiorrhiza debiana is compared with O. cordata, a Chinese species. Detailed description, distribution, ecology, phenology and relevant taxonomic notes are provided along with colour photographs.